Implementation Of Google Site As A School Administration System (A Case Study At UPT SMP Negeri 3 Baebunta, North Luwu Regency) - Kaharman; Chalid Imran Musa; Ed. Farida (Cita konsultindo, 2025)
This research aimed to (1) analyze and describe the implementation of Google Site as a school administration system, and (2) identify the supporting and inhibiting factors of its implementation at UPT SMP Negeri 3 Baebunta. The background of this study is the need for the transformation of school administration from a manual and fragmented system to an integrated digital system to enhance efficiency, transparency, and accountability. This study used a descriptive qualitative approach. Data were collected through in-depth interviews, observations, and documentation with the school principal, vice principal for curriculum, head of administration, school operator, and P5 coordinator. The research findings indicate that the implementation of Google Site successfully designed a centralized and integrated digital administration platform, serving as a